(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Background: Autopsy study is used to disclose many hidden prostatic pathologies and their incidence. The current study aims to evaluate the histopathological pattern of prostatic lesions such as nodular hyperplasia of the prostate, precancerous lesions, and latent cancer in autopsy series of males over the age of 50 and to correlate them with age. Methods: The present study was a prospective autopsy study carried out in the pathology department, after en bloc harvestation of prostate gland from autopsies of men aged more than 50 years by the forensic team of Government Medical College Patiala. Results: Age ranges from 51-90 years and the mean age was 58.57 ± 8.11years. The weight of the prostate gland ranged from 18 to 42 grams with mean weight 27.01 ± 3.34g. Benign prostatic hyperplasia was the common pathological finding (79%), 38 cases of chronic non-specific prostatitis, 3 cases with acute prostatitis and 4 cases were associated with prostatic intraepithelial neoplasia. Prostatic adenocarcinoma was detected in 9 cases. Conclusions: The present study shows that normal prostate gains weight with advancing age. The majority of cases are in the 6th decade, benign prostatic hyperplasia is the most common lesion encountered